Pengaruh Wisata Religi Di Makam Godog Kabupaten Garut Terhadap Peningkatan Kesejahteraan Ekonomi Masyarakat - Syaripudin, Enceng Iip; Bahri, Saepul (STAI Al Musaddadiyah Garut, 2022)
Religious tourism or often referred to as sharia tourism, pilgrimage and halal tourism is a journey to gain experience and lessons (Ibrah). The influence of religious tourism is the occurrence of economic activities that have an impact on improving economic welfare in the community. This is due to the attachment of tourists as consumers to the surrounding community as distributors or producers in meeting needs when traveling. Economic welfare is the methodology of economics in evaluating the economy universally related to welfare. The formulation of the problem in this study is: Does religious tourism at Godog's Tomb affect the economic welfare of the community around the tourist attraction? How is the economic welfare of the community viewed from the perspective of Islamic economics? From the formulation of the problem, the target to be achieved from this study is 1. To find out how the influence of religious tourism at Godog Tomb affects the economic welfare of the community. 2. To determine the economic welfare of the community in terms of the perspective of Islamic economics. The research method used in research is quantitative method. The results of this paper formulate the conclusion that Godog Tomb religious tourism affects the economic welfare of the surrounding community although it is not significant and the economic welfare of the community in Godog Tomb religious tourism is in accordance with the perspective of Islamic economics in the absence of things that contradict the rules in Islamic economic teachings. From the results of the study, it is known from the results of the analysis that the p-value of x is 0.397 meaning that it is not greater than 0.05 so it is not significant. Based on the results of the t test, the effect of the variable x on y is 0.348, which means it is smaller than 0.05. So variable x does not have a significant effect on variable y, thus Ho accepts, that partially tourist visits have a positive but not significant effect on the welfare of the community around the tourist attraction. This shows that tourist visits have a positive but not significant effect on the welfare of the community around the tourist attraction. Keywords: Tourism, Religion, Welfare, Economy